Tobacco Smoking and Colorectal Cancer: A Population-based Case-control Study in Newfoundland and Labrador - Zhao, Jinhui (Can J Public Health, 2010)
OBJECTIVE: Newfoundland and Labrador (NL) has the highest incidence rate of both colorectal cancer (CRC) and smoking prevalence in Canada. The objective of this study was to examine if CRC is associated with smoking in this population. METHODS: Newly diagnosed cases identified between 1999 and 2003 were frequency-matched by 5-year age group and sex with controls selected from the residents of NL through random digit dialing. A total of 702 cases and 717 controls consented to participate in the study and completed a set of self-administered questionnaires. Measures of tobacco use included type of tobacco, age of initiation of smoking, years of smoking, years since started smoking, number of cigarettes smoked daily, pack years, and years since abstention from smoking. Odds ratios were estimated using multivariate logistic regression. RESULTS: In comparison with non-smokers, former and current smokers were at a significantly elevated risk of CRC with corresponding odds ratios of 1.36 and 1.96. The risk significantly increased with cigarette smoking years, the amount of cigarettes smoked daily, and cigarette pack years. The risk significantly decreased with years of abstention from smoking cigarettes. This association was stronger among drinkers and in men. In addition, this effect was observed to be slightly stronger for rectum than colon cancer. DISCUSSION: In summary, cigarette smoking increased the risk of CRC in the NL population. The risk of CRC associated with cigarette smoking varies by sex, drinking status, and site of CRC.